Analisis Efektivitas Pengelolaan Pendapatan Objek Wisata Sawah Pure Tanjung Morawa Deli Serdang - Pertiwi, Tri Bagus; Juliati Nasution, Yenni Samri; Nurwani, Nurwani (ITB AAS INDONESIA Surakarta, 2024)
This research aims to measure the effectiveness of income from the Punden Rejo Tanjung Morawa Deli Serdang rice fields tourist attraction, the type of research used is qualitative research with a descriptive approach. With data collection methods, namely interviews, documentation and observation. This research was conducted to see, assess and analyze the success of pure tourism destination revenue management in increasing regional income. Based on the results of the analysis of the effectiveness of the income of the Punden Rejo rice field tourist attraction, it is said to be less effective because in January it was 99.2%, based on the percentage criteria, the criteria are quite effective, while the percentage of effectiveness is most drastic in November, namely 71% based on the criteria in this percentage. then it is categorized as ineffective. If you look at the percentage in 2023, it is in the less effective category because it shows an average of 76.6%. This is because the number of visitors and income at the Punden Rejo rice field tourist attraction counter has decreased every month. This decrease is possible because there are still problems where human resources have not been maximized in supporting the development of rice field tourism in the village and have not been maximized in organizing financial management and marketing. . income from rice field tourism objects has decreased, thus affecting the effectiveness of tourism income. Promotion to the surrounding community also needs to be strengthened with digital marketing so that progress in managing rice field tourism can be maximized.